Discontinuity g‐modes of hybrid stars: Effect of sequential phase transitions. Issue 1 (1st February 2021) - Rodríguez, Maria Camila; Ranea‐Sandoval, Ignacio F.; Mariani, Mauro; Malfatti, Germán; Guilera, Octavio Miguel
Abstract: The detection of event GW170817 and its electromagnetic counterpart started the era of multi‐messenger astronomy with gravitational waves. The observational constraints from this event and the estimation of mass and radius of PSR J0030 + 0451 is being used to get insights related to the nature of matter inside these compact objects. In this work, we construct hybrid equations of state using modern parametrizations of the relativistic mean field model for the outer core and a generalization of the Constant Speed of Sound parametrization that allow to study sharp sequential phase transitions in the inner core. Moreover, we study non‐radial perturbations of these stellar configurations using the relativistic Cowling approximation. We focus our attention on the g ‐modes that arise due to the sharp phase transitions and show that, due to the second phase transition, a new g ‐mode appears, g 2 ‐mode, with frequencies smaller that ∼0.5 kHz.